Towards a Decentralized Internet: The Interplay of Novel Architectures, Protocols, and Community-Driven Development - Piotr PORZUCZEK (Communications of International Proceedings, 2025)
Platform monopolies have turned the contemporary internet into digital feudalism, extracting profit from human connection while enabling surveillance and censorship. Iran’s 2019 near-blackout, which cut connectivity to 5 %, exposed how centralized architectures become authoritarian chokepoints. Yet scholarship remains fragmented: most studies isolate protocols instead of synthesizing how technical design and political economy co-evolve. We compare federated systems such as ReP2P Matrix, Nostr’s peer-to-peer networks, Bluesky’s AT Protocol, blockchain communication hybrids, and Named Data Networking. Our multi-method study of decentralized internet alternatives blends traffic analytics of 4 million Nostr users on 600 relays, performance benchmarks, economic sustainability modeling, and architectural case studies. We ask whether these designs can fulfil the promise of a truly decentralized internet. The evidence is mixed. SendingNetwork scales group messaging linearly, and Waku proves spam-resistant peer-to-peer networks with <300 ms proof generation; however, no single protocol reconciles censorship resistance, usability, and economic sustainability. Nostr delivers uncompromising censorship resistance yet consumes 35 × the resources of centralized systems. Bluesky’s growth leaves 98.9 % of identities non-portable. Community mesh networks invite new hierarchies of technical privilege. Accepting irreducible trade-offs must guide emerging web3 governance. Communities will choose architectures aligned with their values, but meaningful decentralization will remain aspirational until funding models and accessibility gaps are resolved.
Keywords: Decentralized internet; distributed architectures; federated systems; peer-to-peer networks